Factors Relates to the Members’ Contribution to Group Activities: A Case of Vegetable Growing Group at Baan Non Khawao in Khon Kaen Province - Utaranakorn, Panatda; Mashino, Kodai; Yasunobu, Kumi (Journal of Applied Economics and Management Strategy, 2020)
ABSTRACT The objective of this research was to determine the factors related to members’ contributions to group activities using the following four indices: i) member attributes, ii) managerial orientations, iii) reasons for joining the group, and iv) organizational commitment. The data were collected using individual interviews with 27 members belonging to a vegetable growing group in Baan Non Khawao in Khon Kaen Province in Northeast Thailand. This vegetable group was selected as representative of a longstanding group, indicated by the increasing number of registered members. In order to analyze the influential factors, principal component analysis, correlation coefficients, and descriptive statistics were employed. The results showed that the positive factors related to the members’ contributions to group activities were household income, family labor, the sale of Good Agricultural Practice vegetables, the sale of rice, and farmer managerial orientation regarding both “family members first” and farmer initiatives. Moreover, affective commitment was negatively correlated with the contribution to adjusting shipments. Furthermore, the percentage of dealer use, the farmer’s managerial orientation with regard to sustainable development, and the reasons for joining the group were negatively correlated with cooperation with group management.